2021
DOI: 10.31258/ijebp.v5n1.p39-59
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Reading Strategies in Academic Reading by Indonesian Learners

Abstract: This case study explores the Indonesian learners' reading strategies and identifies high and low-group learners' reading strategies. Semi-structured interviews, questionnaires, and open-ended questions were triangulated for validity and reliability data. Several findings were revealed. The Indonesian learners read critically and varied through cognitive, metacognitive, and affective strategies. They applied more cognitive strategies than metacognitive and affective strategies, which was less helpful and less e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
2
2
Order By: Relevance
“…It could be said that the findings in this study are do not support previous research by Thuy (2018) and Erni (2021) that the students employed more cognitive strategies rather than metacognitive and socio affective ones since this study found that metacognitive was the most strategy that students use over cognitive and socio affective strategies.…”
Section: The Computation Of the Questionnairecontrasting
confidence: 99%
See 2 more Smart Citations
“…It could be said that the findings in this study are do not support previous research by Thuy (2018) and Erni (2021) that the students employed more cognitive strategies rather than metacognitive and socio affective ones since this study found that metacognitive was the most strategy that students use over cognitive and socio affective strategies.…”
Section: The Computation Of the Questionnairecontrasting
confidence: 99%
“…This finding was slightly different from other studies which reported that cognitive strategy use has significant relationship to the students' reading comprehension score (e.g. Erni, 2021;Shang, 2011;Thuy, 2018;Ozek & Civelek, 2006;).…”
Section: Relationship Between Reading Strategy Used and The Reading S...contrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, teachers should equip students with relevant sources, media, and social environments (Nur, 2003) to make learning more successful and fun (Oxford, 1989). The use of wrong reading strategies contributes to students' reading failures (Erni, 2021b). Academic reading requires readers to employ critical and creative thinking skills.…”
Section: A Academic Readingmentioning
confidence: 99%